Mapping and candidate gene analysis of QTLs for grain shape in a rice chromosome segment substitution line Z485 and breeding of SSSLs - You, Jing; Ye, Li; Wang, Dachuan; Zhang, Yi; Xiao, Wenwen; Wei, Mi; Wu, Ruhui; Liu, Jinyan; He, Guanghua; Zhao, Fangming; Zhang, Ting (Molecular breeding, 2024)
Grain shape is one of the most important factors that affects rice yield. Cloning novel grain shape genes and analyzing their genetic mechanisms are crucial for high yield breeding. In this study, a slender grain CSSL-Z485 with 3-segments substitution in the genetic background of Nipponbare was constructed in rice. Cytological analysis showed that the longer grain length of Z485 was related to the increase in glume cell numbers, while the narrower grain width was associated with the decrease in cell width. Three grain shape-related quantitative trait locus (QTLs), including qGL12 , qGW12 , and qRLW12 , were identified through the F 2 population constructed from a cross between Nipponbare and Z485. Furthermore, four single segment substitution lines (SSSLs, S1-S4) carrying the target QTLs were dissected from Z485 by MAS. Finally, three candidate genes of qGL12 for grain length and qGW12 for grain width located in S3 were confirmed by DNA sequencing, RT-qPCR, and protein structure prediction. Specifically, candidate gene 1 encodes a ubiquitin family protein, while candidate genes 2 and 3 encode zinc finger proteins. The results provide valuable germplasm resources for cloning novel grain shape genes and molecular breeding by design.